Psychological adjustment to death anxiety: a qualitative study of Chinese patients with advanced cancer - Xianghua Xu; Wanting Xia; Furong Chen; Meijun Ou (BMJ Open)
Objectives Death anxiety (DA) refers to the negative emotions experienced when a person reflects on the inevitability of their own death, which is common among patients with cancer. It is crucial to understand the causes, coping styles and adjustment processes related to DA. The purpose of this qualitative study is to explore the adaptation process and outcome of patients with advanced cancer with DA and to provide evidence-based support for the development of targeted intervention measures to improve the mental health of such patients.Design This cross-sectional qualitative study sampled patients with advanced cancer (n=20). Grounded theory procedures were used to analyse transcripts and a theoretical model generated.Setting All interviewees in this study were from a tertiary oncology hospital in Hunan Province, China. The data analysis followed the constructive grounded theory method, involving constant comparison and memo writing.Participants A purposive and theoretical sampling approach was used to recruit 20 patients with advanced cancer with diverse characteristics.Results A total of 20 participants were included in the study. Four stages of DA in patients with advanced cancer were extracted from the interview data: (1) death reminder and prominence; (2) perception and association; (3) defence and control; (4) transformation and Acceptance.Conclusions This study highlights the psychological status and coping strategies of dynamic nature of patients with advanced cancer when confronted with negative emotions associated with death. It emphasises the importance of timely identification of DA in psychological nursing for patients with advanced cancer and the need for targeted psychological interventions based on their specific psychological processes.Implications Knowing interventions that aim to promote the integration of internal and external resources, enhance self-esteem and facilitate a calm and accepting attitude towards death could ultimately reduce the overall DA of patients with advanced cancer.